2021
DOI: 10.1080/13511610.2021.1968355
|View full text |Cite
|
Sign up to set email alerts
|

Emotions in the European Union's decision-making: the reform of the Dublin System in the context of the refugee crisis

Abstract: The European Union's decision-making process has mostly been pictured as a technocratic and consensual process with little or no place for the logics of passion. The reform of the Dublin System in the wake of the refugee crisis (2015-16) has been analyzed from different angles but not from a political psychology perspective in which emotions are fully taken into account. Crises are often seen as a window of opportunity because key players engage in a strategic process of sense-making. This article explores the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Studies on European politics have seldom pursued the challenge of theorizing processes in which feelings are formed and structured within social and cultural environments and how emotions are connected to norms and values. From this perspective, only a few case studies have shown that emotions can shape EU decision‐making processes and outcomes (Sanchez Salgado, 2021; 2022; Smith, 2021; Terzi et al, 2021). Emotions have also been used by EU‐based mom‐governmental organizations (NGOs) to justify their policy positions and to influence the policy process (Lynggaard, 2017; Sanchez Salgado, 2018).…”
Section: The European Union: a Rational Non‐political Entity?mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on European politics have seldom pursued the challenge of theorizing processes in which feelings are formed and structured within social and cultural environments and how emotions are connected to norms and values. From this perspective, only a few case studies have shown that emotions can shape EU decision‐making processes and outcomes (Sanchez Salgado, 2021; 2022; Smith, 2021; Terzi et al, 2021). Emotions have also been used by EU‐based mom‐governmental organizations (NGOs) to justify their policy positions and to influence the policy process (Lynggaard, 2017; Sanchez Salgado, 2018).…”
Section: The European Union: a Rational Non‐political Entity?mentioning
confidence: 99%
“…To illustrate with an example, fear has been related to closure and avoidance of risk, while compassion and sympathy motivates us to improve the situation of another (Halperin & Pliskin, 2015). To be more specific, if fear were cultivated within the context of a refugee crisis, perceptions would be shaped accordingly, and the policy solutions that would be put forward would be associated with the closure of borders and neutralization of danger, while other policy solutions, such as opening legal paths to migration would be disregarded (Sanchez Salgado, 2022).…”
Section: Discourse On Emotions In Politics and The Power Of Perceptionmentioning
confidence: 99%
“…However, it failed because of a lack of “a consensus around the (policy) norms underpinning the origin and consequences of a crisis” (Ripoll Servent, 2019, p. 198). In consequence, “the policy solution adopted in 2015 to relocate refugees (based on empathy) was replaced by the decision to close borders and send refugees back to Turkey (based on fear)” (Sanchez Salgado, 2021b, p. 35).…”
Section: Introductionmentioning
confidence: 99%